Optimization of P2 meshes and applications. (July 2020) - Feuillet, Rémi; Loseille, Adrien; Alauzet, Frédéric
Abstract: Mesh optimization techniques are a way to locally modify the mesh in order to improve it with respect to a given quality criterion. To this end, this work presents the generalization of two mesh quality-based optimization operators to P 2 meshes. The generalized operators consist in mesh smoothing and generalized swapping. With the use of these operators, P 2 mesh generation starting from a P 1 mesh is more robust and P 2 connectivity-change moving mesh methods for large displacements are now possible. Graphical abstract: Highlights: The generalization to the degree two of two classic mesh optimization operators. It enables robustness to a linear-elasticity based mesh curving process. It provides an extension to P2 of the connectivity-change moving-mesh methods. Several examples on real-life configurations prove the efficiency of the approach.